Prostytucja i cyberprostytucja jako zagrożenie dla młodych ludzi – raport z badań - Górka, Marek (Studia Edukacyjne, 2020)
The subject of cyberprostitution reflectsthe growing number of socio-political problems stemming from the dynamic development of cybertechonology and its expansion into every area of human life. In the age of cyberrevolution, there is an increase in the number of pornographic social networking sites. The sex industry quickly adopted all new information technologies to increase young people’s access to pornography. As a result of the link between the internet and the sex industry, the border be-tween the current phenomenon of prostitution and its form in cyberspace has blurred. This article, based on the study, discusses the main motivational factors that contribute to the growth of prostitution. The differences between prostitution in the real and virtual worlds are also indicated. The purpose of the study is moreover to show some disturbing phenomena that may have a negative impact – not only on the emotional development of man – but also on shaping future civil society.